2020
DOI: 10.21608/ejhc.2020.166531
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Ostracism and Counterproductive Work Behaviors among Nurses

Abstract: Background:The workplace ostracism phenomenon is taking more attention in the eyes of social researchers and also different studies verified that it has a adverse effect on organizational outcome and also individual behavior and performance. Research Aim: To evaluate workplace ostracism and counterproductive work behaviors among nurses Methodology: A cross sectional design was conducted at Damanhour university hospitals (medical/surgical units and Intensive Care Units (ICU) at Itai El baroud central hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…These findings are in the same line with (33) who found that half of the studied nurses suffered from low WPO. The findings are similar to (34) who reported that two-thirds of studied nurses had a moderate level of WPO and one fifth had low WPO. This is in contrast with (35) who indicated that ostracism is mainly observed in healthcare organizations.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in the same line with (33) who found that half of the studied nurses suffered from low WPO. The findings are similar to (34) who reported that two-thirds of studied nurses had a moderate level of WPO and one fifth had low WPO. This is in contrast with (35) who indicated that ostracism is mainly observed in healthcare organizations.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Mlika et al [54] indicated that ostracism is frequently observed in healthcare organizations. Ebrahim and Eldeep [43] reported that two-thirds of the studied nurses had a moderate level of workplace ostracism and one fifth had low workplace ostracism. They suggested that bias from management, peer jealousy, and actual health problems among nurses were at blame.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, when nurses ostracised by their colleagues, start to feel powerlessness, unhappiness, hostility, and unworthiness, which ultimately cause counterproductive work behaviours. Ostracism caused employees' psychological burden as emotional exhaustion, work tense and these pressures could upset their work and cause work conflict [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…In that study, 57% of staff nurses (N = 100) had a low level of workplace ostracism. In addition, the second recent study by Ahmed and Mahmoud (2020) reported that two-thirds of nurses (N = 349)…”
Section: Discussionmentioning
confidence: 99%
“…In that study, 57% of staff nurses ( N = 100) had a low level of workplace ostracism. In addition, the second recent study by Ahmed and Mahmoud (2020) reported that two‐thirds of nurses ( N = 349) had experienced a moderate level of workplace ostracism. Although we had in this study other professional groups than only nurses, it is possible to examine the results in an indicative way in relation to each other.…”
Section: Discussionmentioning
confidence: 99%